Relationship between the weights of seed beetles of the genus Megacerus Fåhraeus, 1839 (Coleoptera: Chrysomelidae: Bruchinae) and their host seeds of the family Convolvulaceae - Canto, A. (Sci Rep, 2019)
We studied seeds from a set of plant species from the Convolvulaceae family. Seeds collected from natural populations and infested with beetles of genus Megacerus were monitored until the beetle emergence. We analyze the relationship between body weight of beetles and seed weight of host plants, and its connection with between-species differences and sexual dimorphism. The results show that differences in the scaling of body weight of beetles are associated with sexual dimorphism. For the same species of beetle, the females tend to have heavier bodies than the males. Differences between host plants species in the weight of seeds are related to differences in the body weight Megacerus species, resulting in a distinctive pattern of seed infestation across hosts. Small-sized (lighter) species of beetles tended to infest small-sized (lighter) seed species and, correspondingly, heavier beetles species tended to do it in heavier seed species. Mechanisms of female oviposition preferences may be involved to generate that pattern. In general, the beetle weight showed an asymptotic relation with the host seed weight. The greater the weight of the seed, the greater the weight of adult beetle was. However, the proportion in weights reaches an asymptotic value probably because beetles reached the maximum possible weight for their species. We conclude that the process of specialization in the seed-beetle assemblage studied is influenced by intrinsic traits of the species involved in the interaction (beetles and seeds) and by differences between sexes in their sexual-allocation paths.